Maximal fat oxidation rate and cross-over point with respect to lactate thresholds do not have good agreement - Gonzalez-Haro, C. (International Journal of Sports Medicine, 2011)
The present cross-sectional study was designed to assess the agreement between maximal fat oxidation rate (maxFATOXR) vs. Lactate Threshold (LT), and cross-over point (COP) vs. Individual Anaerobic Threshold (IAT) in well-trained athletes. 2 groups of male, well-trained endurance athletes (short-distance triathletes (ST) (n=11), and road cyclists (RC) (n=11)) performed a graded cycle ergometer test to exhaustion, with 4-min stages and 30-W increments. LT, IAT, maxFATOXR and COP were determined for each group. FATOXR and CHOOXR were estimated by means of indirect calorimetry and stoichiometric equations. The agreement between maxFATOXR vs. LT, and COP vs. IAT were determined using the Bland-Altman methodology. In spite of the low systematic error (bias) (high accuracy) for COP vs. IAT, the variable error (limits of agreement) was moderate (moderate precision). For maxFATOXR vs. LT the systematic error was moderate (moderate accuracy), and the variable error was moderate to high (moderate to low precision). In conclusion, the data obtained from this study shows that maxFATOXR and COP do not exhibit good agreement with LT and IAT, in male endurance well-trained athletes. Consequently, it is not possible to assume that maxFATOXR vs. LT and COP vs. IAT occurs at the same exercise intensity.